Hamzah Al-Fansuri: A Figure of Malay-Indonesian Philosophical Mysticism and Sufi Literature - Harahap, Khoirul Amru (International Conference of Moslem Society, 2018)
This paper discusses Hamzah al-Fansuri and his mysticsm philosophical thought and his sufi literature. His mysticism philosopical thought was very controversial that it raises debates in in his era. One of the hardest figure that attack his mysticism philosophical thought was Nuruddin ar-Raniri. This sunni’s mysticism figure considered al-Fansuri a deviate mysticism, zindiq and mulhid (heathen). Mysticism concept he practiced was the concept of wahdah al-wujud or known as wujudiyah concept, which is mostly affected by Ibnu ‘Arabi. Al-Fansuri’s Wujudiyah concept is a concept stating that wujud (existency) is essentially one, even though it seems a lot. All things that are seen a lot by the sense organ, actually just appearance of a form of existency, Allah. However, al-Fansuri separated it between intrinsic form and inherent form. Inherent form is actually nothing, it can be fana’ at every time, and it does not exist without an essential being. Even though he practiced wujudiyah concept, he is strongly refused ittihad concept (the united of the sufi with God) and hulul concept (God put a place from the body of someone). Meanwhile, his sufi literature has 6 characteristics: 1. He used authorship markers. 2. He quoted a lot of verses of Quran, hadith, and Arabic words. 3. He put his name and nick name in the end of his poetry ties. 4. He used imageries and metaphorical symbolic. 5. He was clever in joining diction with rhythm in a balanced way. 6. He was clever in joining metaphysics sense, logical and sufi aesthetic in his poems.